Pengaruh Pendapatan Asli Daerah Terhadap Belanja Daerah Dan Budget Ratcheting Sebagai Variabel Moderasi - Aldy Andrean; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2020)
The variables tested in this study consisted of Regional Original Income as an independent variable measured by the number of several revenue items in the Realized Budget and Regional Expenditure Report as the dependent variable measured by looking at expenditure items in the Realized Budget Report, then Budget Ratcheting as a moderating variable as measured by the Aranda model (2010). The sample in this study was conducted in 19 Regencies / Cities of West Sumatra Province in 2013 - 2017. The results of the study showed that the Local Revenue significantly affected Regional Expenditure and Budget Ratcheting as a moderating variable strengthening the relationship between Own Revenue and Regional Expenditure.